PERANAN BIMBINGAN PERKAWINAN (BIMWIN) DALAM MEMINIMALISIR TERJADINYA PERCERAIAN PADA MASA PASCA COVID-19 DI KOTA MAGELANG - Nur Rofiq; Kuswan Hadji; Mohammad ‘Ulyan (Journal Khafi : Journal Of Islamic Studies, 2023)
Marriage is an inner and outer bond between a man and woman in order to create a happy and blessing full ever after family. In fact, some problems perhaps appear through family lifetime. The aim of this research: to analyze the role of Marriage Guidance and the obstacle of that in minimalizing the divorce cases amid Covid-19 in Magelang. The methodology in this research is descriptive qualitative analysis by field research model. Results: The highly dominant role of Marriage Guidance that is applied by the council on the Religious Affairs Office in minimalizing the divorce. They are the front troopers in helping pre-marriage couple to build strong family in the harmony then they can create sakinah, mawaddah, and rahmah family. The obstacles which is faced by the Religious Affair Offices are still the same, such as; it is hard to invite the pre-marriage couple coming to the office to get the guidance because they have to work and difficult to get off days for the guidance. Contribution to the scientific world: The result of this research can be references for any researcher who has focus on the marriage field, especially pre-marriage couple that did not have enough time to join and get the Marriage Guidance.